Relationship between obesity and dental caries in children - Farith Damián González Martínez; Meisser Vidal Madera Anaya; Lesbia Rosa Tirado Amador (Editorial Ciencias Médicas, 2014)
Oral health has been linked to the presence of some systemic disorders in children and it has been suggested that dental caries are associated with obesity. The objective of this review was to compare the results of the evidence on the relationship between obesity and dental caries in children, so a CT and systematic search was performed using the term "dental caries","obesity", "overweight", and "underweight" in data bases such as Medline, Embase, Pubmed, and Ovid. 439 items were found and 15 articles out of them were selected since they met the inclusion criteria and exceeded an assessment of methodological quality. Findings were stored and organized in a database, they were statistically processed and analyzed considering odds ratios and the Pearson correlation coefficient reported. An overall prevalence of dental caries was 49.6 %; 52.5 % for obese, 46.8 % for non-obese. No association between dental caries and obesity was found in 9 of 15 studies. The consulted evidence suggests that there is no relationship between obesity and dental caries in children, because the prevalence of caries showed no statistically significant differences between obese and non-obese children.